Developing Culturally Responsive Teaching Practices in First Nations Communities: Learning Anishnaabemowin and Land-Based Teachings - Oskineegish, Melissa (Alberta Journal of Educational Research, 2015)
First Nations schools in northern Ontario have the dual responsibility of providing students with the skills and foundation to thrive in their community as well as in higher education outside of their community. This responsibility requires teachers to be capable of developing and implementing lessons that support academic excellence and cultural enrichment. The findings within this article are from a study that asked experienced First Nations and non-Native teachers how non-Native teachers can learn to develop culturally responsive lessons in remote First Nations schools. Within the findings, Anishnaabemowin (Native language) and land-based activities are explored as rich sources for non-Native teachers to learn to develop culturally responsive lessons. The article concludes with a discussion of the importance of linguistic and cultural learning that is in relationship with [LR1] Elders, community members, and students. Les écoles des Premières Nations dans le nord de l’Ontario ont la double responsabilité de fournir aux élèves les habiletés et les assises pour qu’ils puissent s’épanouir à la fois dans leurs communautés et dans des établissements d’enseignement supérieur à l’extérieur de celles-ci. De cette responsabilité découle l’obligation des enseignants de développer et mettre en pratique des leçons qui appuient l’excellence académique et l’enrichissement culturel. Cet article porte sur une étude ayant demandé à des enseignants autochtones et non-autochtones d’expérience comment les enseignants non-autochtones des écoles des Premières Nations dans des régions éloignées pourraient apprendre à développer des leçons adaptées à la culture. Les résultats indiquent que le anishnaabemowin, une langue autochtone, et les activités rattachées aux ressources naturelles constituent d’importantes sources dans lesquelles les enseignants non-autochtones pourraient puiser pour créer des leçons adaptées à la culture. L’article conclut avec une discussion sur l’importance de l’apprentissage linguistique et culturel impliquant les Ainés, les membres de la communautés et les élèves.